Accessibility of Polish and Nordic Cittaslow Towns - Alicja Zawadzka (Barometr Regionalny)
The main objective of this article is to indicate transport accessibility (according to two criteria: fly&60 and 6×60×60) and information accessibility (on the Internet) of all Polish (28 ) and all Nordic (9 ) towns — members of the International Network of Cities Where Living is Good. The research was conducted using non-reactive methods: content analysis and desk research. The analysis has shown that the fly&60 criterion is met by eight Cittaslow towns (seven Polish and one Nordic), and the 6×60×60 criterion — by five towns (four Polish and one Nordic), which confirms the thesis on the peripheral nature of Cittaslow cities, which in fact may be perceived as an attracting factor. Their location, away from frequently used routes, may attract (some of them already do so) tourists seeking alternative forms of leisure, following a growing global trend of sustainable tourism. The level of accessibility to online information on the Cittaslow towns is varied, but rather low.